Buddhist law in Burma: a history of Dhammasattha texts and jurisprudence, 1250-1850 - Lammerts, Dietrich Christian (University of Hawaiʻi Press, 2018)
Buddhist law in Burma -- Before the law : traces of dhammasattha in Buddhist legal and textual culture, c. 1250-1600 -- Dhammavilasa : legal text and cosmology in the early seventeenth century -- Manusara : history, jurisdiction, authorship -- Dhammasattha and its discontents, 1681-c.1850 -- Conclusion : Sakka's thunderbolt